Intuiciones de criptojudaísmo en el Quod nihil scitur de Francisco Sánchez - Bermúdez Vázquez, Manuel (Contrastes. Revista Internacional de Filosofía, 2007)
RESUMEN En la obra del pensador gallego Francisco Sánchez (1551-1623), titulada Que nada se sabe, existen una serie de características que nos obligan a relacionarla directamente con el pensamiento judío. Entre estas cuestiones se hallan: las citas bíblicas recogidas por su autor, siendo la gran mayoría de ellas procedentes del Antiguo Testamento; la falta de la dedicatoria a la virgen María o la relación entre el alma y el cuerpo que recoge Sánchez y que es de claro origen judío. PALABRAS CLAVE ESCEPTICISMO, PENSAMIENTO JUDÍO, FRANCISCO SÁNCHEZ ABSTRACT In the work of the thinker Francisco Sanchez (1551-1623), entitled That nothing is known, there are some characteristics that force us to directly relate it to the Jewish thought. Some of these questions are: the Biblical quotations gathered by its author, coming the great majority of them from the Old Testament; the lack of the dedication to Virgin Mary or the relation between the soul and the body that Sanchez shares with the Jewish tradition. All these topics point at the importance of this tradition in the work That nothing is known. KEYWORDS SCEPTICISM, JEWISH THOUGHT, FRANCISCO SANCHEZ, RENAISSANCE